Design and implementation of thermal imging system [electronic resource] - Tengku Ahmad Iskandar T. Alang, 1991-, author (2014)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2014